2005
DOI: 10.2174/156720305775009643
|View full text |Cite
|
Sign up to set email alerts
|

Cognition-Enhancing Drugs in Mild Cognitive Impairment (MCI) and Alzheimers Disease (AD): An Update [1]

Abstract: Cognition enhancers are drugs able to facilitate attentional abilities and acquisition, storage and retrieval of information, and to attenuate the impairment of cognitive functions associated with head traumas, stroke, age and agerelated pathologies such as MCI and AD. Development of cognition enhancers is still a difficult task because of the complexity of the brain functions, poor predictivity of animal tests and lengthy and expensive clinical trials. Current research is based on several working hypotheses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 146 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…The different families of cognition enhancers have been reviewed [20][21][22][23][24][25][26] . As far as piracetam-like nootropics are concerned, the lack of a common mechanism of action has been one of the main obstacles to their acceptance as drugs.…”
Section: The Problem Of the Mechanism Of Actionmentioning
confidence: 99%
“…The different families of cognition enhancers have been reviewed [20][21][22][23][24][25][26] . As far as piracetam-like nootropics are concerned, the lack of a common mechanism of action has been one of the main obstacles to their acceptance as drugs.…”
Section: The Problem Of the Mechanism Of Actionmentioning
confidence: 99%
“…Among others, histaminergic (3), ó 1 (35), and glutamatergic (9) receptor systems continue to be explored as targets for cognition enhancing drugs. In particular, allosteric modulators of the AMPA receptor (6,20,24,39) seem to be promising as neuroprotectors and cognition enhancing agents. Piracetam-like compounds, also called nootropics, characterized by a 2-pyrrolidinone structure, also interact, directly or indirectly, with receptors but they suffer from the lack of a common, generally accepted mechanism of action, which has precluded so far a wide acceptance of these drugs as useful medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Piracetam-like compounds, also called nootropics, characterized by a 2-pyrrolidinone structure, also interact, directly or indirectly, with receptors but they suffer from the lack of a common, generally accepted mechanism of action, which has precluded so far a wide acceptance of these drugs as useful medicines. Ironically, the very low toxicity of this class of compounds is itself a problem since it has been considered the result of insufficient activity, even if they are active in most preclinical assays and, at least in some clinical trials, their therapeutic efficacy has been found significant (10,18,20,21).…”
Section: Introductionmentioning
confidence: 99%